Analysis of Shotokan karate techniques actions used by Lithuanian junior national team - Ivaskiene, V.; Grincevicius, A.; Sajute, J.; Rudas, E.; Sriubas, S. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
Ziel der Studie war die Untersuchung der Verteilung und der Effizienz technischer Aktionen der Arme und Beine litauischer Shotokan-Karateka der Juniorennationalmannschaft.